2020
DOI: 10.1116/6.0000685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the frequency and nature of erroneous x-ray photoelectron spectroscopy analyses in the scientific literature

Abstract: This study was undertaken to understand the extent and nature of problems in x-ray photoelectron spectroscopy (XPS) data reported in the literature. It first presents an assessment of the XPS data in three high-quality journals over a six-month period. This analysis of 409 publications showing XPS spectra provides insight into how XPS is being used, identifies the common mistakes or errors in XPS analysis, and reveals which elements are most commonly analyzed. More than 65% of the 409 papers showed fitting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…The C (1s) core-level spectrum of graphitic carbon, such as that of HOPG, is characterized by an asymmetric peak shape with a binding energy typically reported as 284.5 eV (although values between 284.3 and 284.6 eV have been reported [12,14]) and a characteristic π-π* shake-up structure with structure centered around 291 and 294.5 eV (Figure 1). The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in may published papers. Recently, Linford et al [11] reported a method for fitting the C (1s) envelope of graphitic carbon materials, using a reference spectrum of clean graphite/HOPG as a model for the graphitic backbone.…”
Section: The C (1s) Spectrum Of Diamond Hopg and Graphitic Carbonsmentioning
confidence: 99%
“…The C (1s) core-level spectrum of graphitic carbon, such as that of HOPG, is characterized by an asymmetric peak shape with a binding energy typically reported as 284.5 eV (although values between 284.3 and 284.6 eV have been reported [12,14]) and a characteristic π-π* shake-up structure with structure centered around 291 and 294.5 eV (Figure 1). The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in may published papers. Recently, Linford et al [11] reported a method for fitting the C (1s) envelope of graphitic carbon materials, using a reference spectrum of clean graphite/HOPG as a model for the graphitic backbone.…”
Section: The C (1s) Spectrum Of Diamond Hopg and Graphitic Carbonsmentioning
confidence: 99%
“…In the first, all of the peaks, except the one modeling the shake-up signal, were constrained to have the same width. While this restriction should increase the likelihood that physically reasonable results will be obtained (widely varying peak widths in an XPS peak fit are often a sign of poor fitting [18], the box plot summarizing the results of performing this fit with 32 different/random initial conditions (Figure 3c), suggests that these constraints do not lead to a robust fit. That is, the widths of the boxes in Figure 3c indicate that multiple, local minima are present in this fit space.…”
Section: Resultsmentioning
confidence: 99%
“…40 % of the fitted XPS data in the literature is significantly flawed. [18] Other concerns regarding XPS include inappropriate data acquisition and archiving. [19] These issues are part of the so-called reproducibility crisis in science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…% (composition and stoichiometry) can be estimated. This represents the most extended use of XPS, although too often, the popularity and accessibility of the technique leads to incorrect interpretations [34].…”
Section: Resultsmentioning
confidence: 99%